Utilizing the health belief model to examine and promote blood lead screening for clients enrolled in the Trempealeau county women, infant and children (WIC) program - Thill, Nicole (My University, 2013)
Childhood lead poisoning is a serious public health issue. Just last year the Centers for Disease Control and Prevention (CDC) lowered the blood lead level of concern from 10 mcg/dL to 5 mcg/dL. As a result, the number of children with elevated blood lead levels increased substantially. This report will apply the Health Belief Model to lead poisoning and lead testing among children enrolled in Trempealeau County's Women, Infant, and Children (WIC) program. This was done through examining the literature as well as conducting key informant interviews among Trempealeau County Health Department staff and parents of children enrolled in the WIC program. The information collected was then used to create an educational video, poster, and brochure, which were available at the WIC clinics in Whitehall, WI. Additionally, surveys were handed out to determine if the materials were effective in educating parents on lead poisoning and lead testing based upon the Health Belief Model. The ultimate goal of this project was to educate WIC parents on the dangers of lead poisoning, and promote blood lead testing.
Keywords: Lead based paint - Government policy - Wisconsin; Lead poisoning in children - Wisconsin.